Eu+3-doped chalcone substituted cyclotriphosphazenes: Synthesis, characterizations, thermal and dielectrical properties - Koran, Kenan; Özen, Furkan; Biryan, Fatih; Demirelli, Kadir; Görgülü, Ahmet Orhan (My University, 2016)
A series of new cyclotriphosphazene derivatives (2a-e) were prepared from the reactions of substituted chalcone compounds (1a-e) containing different organic side groups at para position with cyclotriphosphazene (2) bearing dioxybiphenyl. The structures of 2a-e were approved by microanalysis and spectroscopic techniques (MS, FT-IR, 31P, 1H, 13C, and 13C-APT NMR). The thermal behaviors of compounds 2a-e were investigated by thermogravimetric analysis (TGA). These compounds were found to be stable up to about 300 °C. Dielectric properties of 2a-e were measured against temperature (between 25 and 160 °C at 1 kHz) and frequency (range from 100 Hz to 5 kHz at 25 °C) using means of an impedance analyzer. Among them dielectric properties of methoxy substituted cyclotriphosphazene 2e were found to be higher than other phosphazenes. The compound 2b, which has the lower dielectric property values than other phosphazenes, was selected to determine the influence of Eu+3-doping on the dielectric properties of phosphazenes and doped with Eu+3 at different mole ratios. At the dielectric properties of Eu+3-doped compound 2b (with increasing molar ratios of Eu+3) was observed an excellent increasing according to Eu+3-undoped phosphazene compounds.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Cyclotriphosphazene; Chalcone–phosphazene; Dielectric property; Europium III